Are guilt and shame in male forensic patients associated with treatment motivation and readiness?. (29th January 2019) - Fuller, Jeannette; Tapp, James; Draycott, Simon
Abstract: Background: Motivation and readiness to change are important drives for forensic patients accessing interventions. It is thought that guilt and shame influence these drives, but to date, their relationship has not been empirically tested. Aims and Hypotheses: The aim of this study is to investigate associations between guilt, shame, and treatment motivation and readiness in a sample of men in a secure hospital. It was hypothesised that guilt would be positively correlated, and shame negatively correlated, with treatment motivation and readiness. Methods: Sixty‐six adult male patients detained in a secure hospital completed the assessments of experiences of guilt, shame, motivation, and readiness for treatment. Clinician‐rated readiness ratings were also collected. Results: Shame proneness showed no significant association with motivation for change or treatment readiness. Guilt proneness and offence‐related shame were positively correlated with treatment readiness. Offence‐related guilt was positively correlated with both motivation and readiness. Regression modelling indicated offence‐related guilt had a significant level of explanatory power. Conclusions and Implications for Practice: This first study of the impact of guilt and shame on motivation and readiness for change among offender hospital inpatients found that offence‐related guilt may be helpful but did not replicate the potential disadvantage of shame. Further research would be warranted into whether the "newness" or the extent of shame may be more important than shame more generally. Given the probable importance of offence‐related guilt, we recommend that guilt attribution is assessed in offender patients to optimise nature and timing of treatment.